Multilateral political governance : a programmatic profile. (2021)
Abstract: The aim of this article is to apply a triadic analytical scheme to the study of the governance of the international system, as an alternative to unidimensional and dichotomous approaches. The latter give rise to reductionist assessments, as they do not reveal the dynamism and complexity of the global social reality. The methodological approach is of a qualitative nature, used to analyse the international system and establish the diagnosis of the play of forces to which it owes its impetus, as a resource to validate the hypothesis of potential change in global economic governance. On the basis of the diagnosis or interpretation, we proceed to the heuristic exercise of seeking alternatives to the current governance of the international system. The main findings are: i) the predominance of economic and financial power over political and cultural power in contemporary globalisation, which imbues the international system with entropic governance; ii) the possibility of establishing corrections to the entropic course through the empowerment of multilateral governance; iii) the need to reform and strengthen the United Nations as the governing entity of multilateral political governance. These normative orientations serve as criteria for the design of foreign policy.